In vitro evaluation of dioscin and protodioscin against ER-positive and triple-negative breast cancer - Najat Bouchmaa; Reda Ben Mrid; Youssef Bouargalne; Sana Ajouaoi; Francesco Cacciola; Rachid El Fatimy; Mohamed Nhiri; Abdelmajid Zyad (PLoS ONE, 2023)
Women’s breast cancer is one of the most significant healthcare issues for the human race that demands a proactive strategy for a cure. In this study, the cytotoxic activity (MTT assay) of two natural steroidal compounds, protodioscin and dioscin, against two major subtypes of human breast cancer estrogen receptor-positive (ER-positive)/MCF-7 and triple-negative breast cancer (TNBC)/MDA-MB-468), was assessed. The clonogenic capacity was evaluated using the clonogenic assay. Oxidative stress was determined by measuring the formation of malondialdehyde and H2O2 and the assessment of total antioxidant enzyme activities (SOD, GPx, GR, and TrxR). Protodioscin and dioscin were highly cytotoxic against the tested cell lines (1.53 μM <IC50< 6 μM) with low cytotoxicity on normal cells (PBMC; IC50 ≥ 50 μM). Interestingly, these compounds were responsible for a substantial decrease in the clonogenic capacity of both cell lines. Moreover, dioscin was able to reduce the cell motility of the invasive breast cancer cells (MDA-MB-468). At the molecular level, the two treatments resulted in an increase of reactive oxygen species. Notably, both compounds were responsible for decreasing the enzymatic activities of glutathione reductase and thioredoxin reductase. On the basis of such considerations, protodioscin and dioscin may serve as promising natural compounds to treat TNBC and ER-positive breast cancer through the induction of oxidative stress.